Students’ critical consciousness through critical literacy awareness - Koo, Yew Lie; Wong, Fook Fei; Kemboja Ismail (Penerbit UKM, 2012)
To think critically is undeniably one of the major elements of “first class human capital” in a knowledge economy. It is most regrettable that Malaysian students, even at the tertiary level, tend to be uncritical due to socialisation processes in the educational and sociocultural environment. Responding to this identified need to raise the critical consciousness of students, this paper examines how a Higher Education teacher challenged her postgraduate students to be critical learners through the use of CLA (Critical literacy awareness) strategies in her Language and Literacy course. The paper suggests that the use of CLA strategies has increased student engagement and strengthened student voices. This paper concludes by proposing that CLA should be included in pedagogical practices in Higher Education given that active participation in knowledge economies is the vision of the Malaysian Higher Education Action Plan (MoHE 2007a, b).